2019
DOI: 10.3390/nu11122990
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Dietary Fatty Acids on Immune Responses

Abstract: Diet-derived fatty acids (FAs) are essential sources of energy and fundamental structural components of cells. They also play important roles in the modulation of immune responses in health and disease. Saturated and unsaturated FAs influence the effector and regulatory functions of innate and adaptive immune cells by changing membrane composition and fluidity and by acting through specific receptors. Impaired balance of saturated/unsaturated FAs, as well as n-6/n-3 polyunsaturated FAs has significant conseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
169
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(179 citation statements)
references
References 357 publications
(635 reference statements)
4
169
0
6
Order By: Relevance
“…Another important mediator involved in the immune response and influenced by nutrition are fatty acids, in particular, ω-3 PUFAs [67,68]. In fact, during bacterial and viral infections, they are able to act on immune cells and regulate diverse inflammatory processes.…”
Section: ω-3 Pufas and Lung Infectionsmentioning
confidence: 99%
“…Another important mediator involved in the immune response and influenced by nutrition are fatty acids, in particular, ω-3 PUFAs [67,68]. In fact, during bacterial and viral infections, they are able to act on immune cells and regulate diverse inflammatory processes.…”
Section: ω-3 Pufas and Lung Infectionsmentioning
confidence: 99%
“…Several in vitro studies also demonstrated that unsaturation fatty acids could exert immunosuppressive effects on T cells, such as reducing its proliferation and activation in a dose-dependent manner [37,40]. However, saturation fatty acids, such as palmitic acid, have been described as essential factors promoting T cell activation and cytokine secretion [41]. In addition, considerable evidence has shown that polyunsaturated fatty acids can modify mast cell functions and suppress its activation then reduce the production of cytokine or chemokine through receptors [42].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the disturbed energy balance in favor of fat accumulation, that is obesity, leads to a WAT growth with hypertrophy and death of adipocytes promoting macrophage infiltration to phagocytize the remains; these in turn produce pro-inflammatory cytokines that favor further infiltration ( 217 , 218 ). Saturated fatty acids directly stimulate differentiation to a pro-inflammatory macrophage profile while monounsaturated and polyunsaturated fatty acids promote an anti-inflammatory profile ( 219 ). Thus, if the stimulus persists, that is, if the diet is still rich in saturated fatty acids and energy, a vicious circle is established with continuous infiltration of pro-inflammatory macrophages, which maintains the inflammation chronically ( 220 ).…”
Section: Metabolic Syndrome: Definitionmentioning
confidence: 99%